Belle [videorecording (Blu-ray + DVD)] - Hosoda, Mamoru, 1967-; Hosoda, Mamoru, 1967- (GKids, 2022)
When a shy high school student enters a virtual world where she becomes a popular singer, one of her concerts is interrupted by a dragon, but as a group of vigilantes hunt the dragon, she sets out to learn more about him.